TLR4 Response to LPS Is Reinforced by Urokinase Receptor - Kiyan, Yulia; Tkachuk, Sergey; Rong, Song; Gorrasi, Anna; Ragno, Pia; Dumler, Inna; Haller, Hermann; Shushakova, Nelli (Frontiers in Immunology, 2020)
GPI-anchored uPAR is the receptor for the extracellular serine protease urokinase-type plasminogen activator (uPA). Though uPAR role in inflammatory processes is documented, underlying mechanisms are not fully understood. In this study we demonstrate that uPAR is a part of Toll-like receptor 4 (TLR4) interactome. Downregulation of uPAR expression resulted in diminished LPS-induced TLR4 signaling, less activation of NFκB, and decreased secretion of inflammatory mediators in myeloid and non-myeloid cells in vitro. In vivo uPAR-/- mice demonstrated better survival, strongly diminished inflammatory response and better organ functions in cecal ligation and puncture mouse polymicrobial sepsis model. Mechanistically, GPI-uPAR and soluble uPAR colocalized with TLR4 on the cell membrane and interacted with scavenger receptor CD36. Our data show that uPAR can interfere with innate immunity response via TLR4 and this mechanism represents a potentially important target in inflammation and sepsis therapy.